Molecular mechanisms of histone deacetylases and inhibitors in renal fibrosis progression - Wang, Jiayu; Li, Jiaxing; Zhang, Xin; Zhang, Min; Hu, Xiaopeng; Yin, Hang (Frontiers in Molecular Biosciences, 2022)
Renal fibrosis is a common progressive manifestation of chronic kidney disease. This phenomenon of self-repair in response to kidney damage seriously affects the normal filtration function of the kidney. Yet, there are no specific treatments for the condition, which marks fibrosis as an irreversible pathological sequela. As such, there is a pressing need to improve our understanding of how fibrosis develops at the cellular and molecular levels and explore specific targeted therapies for these pathogenic mechanisms. It is now generally accepted that renal fibrosis is a pathological transition mediated by extracellular matrix (ECM) deposition, abnormal activation of myofibroblasts, and epithelial-mesenchymal transition (EMT) of renal tubular epithelial cells under the regulation of TGF-β. Histone deacetylases (HDACs) appear to play an essential role in promoting renal fibrosis through non-histone epigenetic modifications. In this review, we summarize the mechanisms of renal fibrosis and the signaling pathways that might be involved in HDACs in renal fibrosis, and the specific mechanisms of action of various HDAC inhibitors (HDACi) in the anti-fibrotic process to elucidate HDACi as a novel therapeutic tool to slow down the progression of renal fibrosis.